Pengaruh Pupuk Hayati Dengan Bahan Pembawa dan NPK Tunggal Terhadap Tinggi Tanaman Dan Berat Gabah Bernas Padi Gogo Inceptisols Jatinangor - Fera Siti Meilani; Reginawanti Hindersah; Mieke Rochimi Setiawati; Fiky Yulianto Wicaksono; Pujawati Suryatmana (Dept Ilmu Tanah & Sumberdaya Lahan Fakultas Pertanian Universitas Padjadjaran, 2023)
Biofertilizers contain bacteria that can offset the use of inorganic fertilizers. However, using bacteria as biofertilizers also requires carrier materials such as bran, compost, and Azolla flour to maintain the viability of the bacteria before being transferred to the soil. This study aimed to determine the effect of consortium biofertilizer with different carriers and doses of NPK (nitrogen, phosphorus, potassium) fertilizer on the growth and yield of upland rice on Inceptisols from Jatinangor. This study used a randomized block design with two factors: the carrier of consortium biofertilizer (compost, rice bran, and Azolla) and the dose of NPK fertilizer (0%, 50%, and 100%). The experimental results showed no interaction between the consortium's biofertilizers with carrier and NPK fertilizer doses on plant height, number of tillers, weight of rice grain, and weight of 100 grains of upland rice plants. The independent factor of biological fertilizer with carrier material significantly affected plant height, and the independent factor of single NPK fertilizer significantly affected plant height, number of tillers, and rice grain weight.